2023
DOI: 10.1111/ejh.13950
|View full text |Cite
|
Sign up to set email alerts
|

Up‐front autologous hematopoietic stem cell transplantation after first complete remission improved prognosis of advanced extra‐nodal NKT cell lymphoma: A multicenter real‐world study in China

Abstract: Objectives The advanced extra‐nodal NK/T‐cell lymphoma (ENKTL) is highly aggressive and lacks effective treatment with a poor prognosis. This study aimed to investigate the effectiveness and safety of autologous hematopoietic stem cell transplantation (ASCT) in CR1. Methods Forty of 121 patients with advanced ENKTL from four Chinese hospitals between January 2006 to December 2021 who achieved first complete remission (CR1) and received at least 4 cycles chemotherapy, were enrolled for analysis. Twenty patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These outcomes do not appear significantly different from those achieved with asparaginase-containing regimens alone. While Gao et al 22 suggested up-front ASCT after CR1 may improve the prognosis for advanced extranodal NK/TCL, their study was retrospective and small, with non-comparable patient characteristics between the ASCT and non-ASCT groups. In our PSM study, NK/TCL patients achieving CR after first-line treatment showed no apparent benefit from ASCT, with all clinical outcomes being comparable between ASCT and non-ASCT.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These outcomes do not appear significantly different from those achieved with asparaginase-containing regimens alone. While Gao et al 22 suggested up-front ASCT after CR1 may improve the prognosis for advanced extranodal NK/TCL, their study was retrospective and small, with non-comparable patient characteristics between the ASCT and non-ASCT groups. In our PSM study, NK/TCL patients achieving CR after first-line treatment showed no apparent benefit from ASCT, with all clinical outcomes being comparable between ASCT and non-ASCT.…”
Section: Discussionmentioning
confidence: 94%
“…These outcomes do not appear significantly different from those achieved with asparaginase‐containing regimens alone. While Gao et al 22 . suggested up‐front ASCT after CR1 may improve the prognosis for advanced extra‐nodal NK/TCL, their study was retrospective and small, with non‐comparable patient characteristics between the ASCT and non‐ASCT groups.…”
Section: Discussionmentioning
confidence: 94%
“…Liu et al 30 conducted large‐scale retrospective studies and reported that only 13 out of 336 (3.9%) newly diagnosed advanced‐stage patients received auto‐HSCT after their first remission, among which 12 patients remained in remission with a mOS of 43.0 months. Gao et al 39 retrospectively reported that upfront HSCT consolidation significantly improved PFS (2‐year PFS: 56% vs 26%, P = .026) and OS (2‐year OS: 61% vs 26%, P = .018) in 40 newly diagnosed advanced‐stage patients. Fox et al 40 retrospectively collected 28 ENKTL patients treated with high‐dose chemotherapy and auto‐HSCT, and the 2‐year PFS and OS rates of the 10 advanced‐stage patients were 33% and 40%, respectively.…”
Section: Discussionmentioning
confidence: 99%